Physicochemical characteristics of whole wheat flour fortified with four different levels of Tricalcium Phosphate - Warrier, Shreya; Pangerkar, Pranali; Randive, Nidhi; Ramesh, Anuradha; Madan, Jagmeet; Rao, Prakash; Udipi, Shobha A. (International Journal of Current Research and Review, 2025)
Introduction: Dietary calcium intakes have been reported to be lower than recommended intakes in women and adolescents. This essential nutrient has not received adequate attention at the population level. Food fortification, particularly of staples can help bridge the gap between requirement and customary intakes, without altering diet patterns. Aim/Objectives: This study aimed to fortify wheat flour to increase calcium content, using four levels of Tri Calcium Phosphate (TCP), to determine the optimum level, based on physicochemical characteristics. Methods: Wheat flour was fortified with four levels of TCP such that 150g of flour would provide 200mg, 300 mg, 400 mg or 500 mg. Physicochemical properties (Water absorption capacity, swelling power, swelling volume, solubility index, bulk density, solvent retention capacity, particle size) were analyzed in fortified and unfortified flour samples. Results: Fortified flours had lower water absorption capacity than unfortified wheat flour (p<0.000). The solubility index (p<0.000) for fortified flours was 1-5% lower than the unfortified flour. Bulk density for all flours was 0.40- 0.42 g/ml. Particle size (p<0.000) and water retention increased with increasing amount of TCP. Overall, the physicochemical characteristics of the fortified samples did not differ from the unfortified wheat flour. Thus, the fortified wheat flour could be used in various processed foods. Conclusions: This is one of the few studies to have attempted fortifying wheat flour to provide about 50% of the EAR from 150g of wheat flour. The study showed that TCP addition did not adversely affect physicochemical characteristics, making it a suitable fortificant for wheat flour.